How to Establish a Tax Policy Unit - Grote, Martin (IMF How To Notes; How-To Note, 2017)
This paper explores that in developing economies, sufficient tax revenue is necessary to finance spending on health care, education, and infrastructure-all of which are prerequisites for economic growth and development. However, it is not simply the revenue ratio that matters; the quality of the revenue system is also essential for delivering fair and efficient outcomes. To design a revenue system that fosters sustainable economic and social development and enjoys broad public support, it is essential for tax reform proposals to be carefully assessed, quantitatively analyzed, and openly debated. This requires that decision makers and all stakeholders in the debate have access to the best available facts, data, and independent evidence-based analysis, including about the impact of tax reforms on revenue, the income distribution, and economic performance. The central institutional actor in the decision making process-the executive-is best supported in this process by what is generally called a tax policy unit (TPU). TPUs are tasked to guide and inform the tax policy debate, based on facts, independent data analysis, and multidisciplinary efforts.